Upaya Peningkatan Minat Belajar Ski Melalui Metode Talking Stick di Kelas X MAN I Langkat - Satria Wiguna (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2019)
The purposes of this study are 1) To determine the learning interest of X MAN 1 Langkat students in the subject of Islamic Cultural History, 2) To determine the use of the talking stick method in teaching and learning activities in the subject of Islamic Cultural History for Class X MAN 1 students. Langkat, 3) To find out the increase in learning outcomes of Islamic Cultural History by using the talking stick method in the subject of Islamic Cultural History for class X students of MAN 1 Langkat. Students' interest in learning at MAN 1 Langkat class X in the SKI subject is very good and has increased after conducting research for two cycles. The use of the talking stick method in this study is online or online learning during the implementation of the second cycle, but it can increase student interest in learning well. In the learning process in cycle II the teacher changes the use of the method because the school implements online learning, but it still produces satisfying student interest in learning because the researcher or teacher always motivates and facilitates student learning activities. The use of the talking stick method can increase student interest in learning at MAN 1 Langkat class X in SKI subjects, which can be seen from the increase in each cycle. The use of the talking stick method with the percentage of students who completed learning in cycle 1 was 58% and cycle II was 84% ​​or an increase of 26%. There was an increase in student learning outcomes in cycle 1 by 68% and cycle II 81% which experienced an increase of 13%. . And the average increase in the percentage of teacher activity in the application of the talking stick method in cycle 1 was 78% and in cycle II was 81% or an increase of 3%.